2009
DOI: 10.1590/s0102-09352009000500030
|View full text |Cite
|
Sign up to set email alerts
|

Frequência de anticorpos anti-Toxoplasma gondii em suínos abatidos sem inspeção em Belém

Abstract: Frequência de anticorpos anti-Toxoplasma gondii em suínos abatidos sem inspeção em Belém [Serologic diagnosis of Toxoplasma gondii in swines slaughtered without inspection in Northern Brazil]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…Our occurrence data corroborates with similar studies performed in other Brazilian states such as Pará (50.0%; Freitas et al 2009) and São Paulo (48.0%; Villalobos et al 2011). However, the occurrence of toxoplasmosis in pigs found in this study was higher than those observed in previous studies: 36.2% in Paraíba (Azevedo et al 2010); 26.9% in Alagoas (Valença et al 2011); 18.2% in Bahia (Bezerra et al 2009); 12.8% in Mato Grosso (Muraro et al 2010); 12.6% in Paraná (Santos et al 2015) and 12.5% in Pernambuco (Fernandes et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Our occurrence data corroborates with similar studies performed in other Brazilian states such as Pará (50.0%; Freitas et al 2009) and São Paulo (48.0%; Villalobos et al 2011). However, the occurrence of toxoplasmosis in pigs found in this study was higher than those observed in previous studies: 36.2% in Paraíba (Azevedo et al 2010); 26.9% in Alagoas (Valença et al 2011); 18.2% in Bahia (Bezerra et al 2009); 12.8% in Mato Grosso (Muraro et al 2010); 12.6% in Paraná (Santos et al 2015) and 12.5% in Pernambuco (Fernandes et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Blood samples were collected and the seraum obtained was used to detect IgG antibodies against T. gondii by ELISA, as described by Silva et al, (1997 (PERDONCINI et al, 2010); 25.5% in Paraná (MILLAR et al, 2008) and 50% in Belém (FREITAS et al, 2009). Animals tested positive for T. gondii were detected in all the analyzed cities.…”
Section: Introductionmentioning
confidence: 99%
“…Slaughterhouse without inspection may receive animals from dubious origin which could had higher prevalence of diseases due to poor hygiene conditions, which was not observed in the present study. Such data is difficult to compare since most of the studies deal only with pigs from abattoir with inspection (Carletti et al, 2005;Feitosa et al, 2014), although in Pará state previous report show 50% prevalence from animals slaughtered without inspection (Freitas et al, 2009). T. gondii and N. caninum infection were associated with the presence of its respective definitive host in the farms (Dubey, 2009;Gui et al, 2020).…”
Section: /9mentioning
confidence: 99%
“…Toxoplasma gondii is an intracellular protozoan that is distributed worldwide and is capable of infecting birds and mammals, including humans, with an estimated global seroprevalence of 19% (95% confidence interval [CI]: 17-22%) in pigs (Foroutan et al, 2019). In the Amazon region, serological studies have already demonstrated the prevalence of T. gondii in wild animals (Minervino et al, 2010;Soares et al, 2011;Vitaliano et al, 2015) including primates (Minervino et al, 2017), dogs (Valadas et al, 2010;Minervino et al, 2012), horses (Moreira et al, 2019) and pigs (Cavalcante et al, 2006;Freitas et al, 2009;Sousa et al, 2014). To our best knowledge, there is only one report on the occurrence of T. gondii antibodies in pigs in Pará State, which was limited to the municipality of Belém (Freitas et al, 2009), and reported that 50% (55/110) of the tested animals were seropositive.…”
Section: Introductionmentioning
confidence: 99%